Mannan oligosaccharides alleviate oxidative injury in the head kidney and spleen in grass carp (Ctenopharyngodon idella) via the Nrf2 signaling pathway after Aeromonas hydrophila infection - Zhiyuan Lu; Lin Feng; Weidan Jiang; Pei Wu; Yang Liu; Jun Jiang; Shengyao Kuang; Ling Tang; Shuwei Li; Chengbo Zhong; Xiaoqiu Zhou (Journal of Animal Science and Biotechnology, 2023)
Abstract Background Mannan oligosaccharides (MOS) are recommended as aquaculture additives owing to their excellent antioxidant properties. In the present study, we examined the effects of dietary MOS on the head kidney and spleen of grass carp (Ctenopharyngodon idella) with Aeromonas hydrophila infection. Methods A total of 540 grass carp were used for the study. They were administered six gradient dosages of the MOS diet (0, 200, 400, 600, 800, and 1,000 mg/kg) for 60 d. Subsequently, we performed a 14-day Aeromonas hydrophila challenge experiment. The antioxidant capacity of the head kidney and spleen were examined using spectrophotometry, DNA fragmentation, qRT-PCR, and Western blotting. Results After infection with Aeromonas hydrophila, 400–600 mg/kg MOS supplementation decreased the levels of reactive oxygen species, protein carbonyl, and malonaldehyde and increased the levels of anti-superoxide anion, anti-hydroxyl radical, and glutathione in the head kidney and spleen of grass carp. The activities of copper-zinc superoxide dismutase, manganese superoxide dismutase, catalase, glutathione S-transferase, glutathione reductase, and glutathione peroxidase were also enhanced by supplementation with 400–600 mg/kg MOS. Furthermore, the expression of most antioxidant enzymes and their corresponding genes increased significantly with supplementation of 200–800 mg/kg MOS. mRNA and protein levels of nuclear factor erythroid 2-related factor 2 also increased following supplementation with 400–600 mg/kg MOS. In addition, supplementation with 400–600 mg/kg MOS reduced excessive apoptosis by inhibiting the death receptor pathway and mitochondrial pathway processes. Conclusions Based on the quadratic regression analysis of the above biomarkers (reactive oxygen species, malondialdehyde, and protein carbonyl) of oxidative damage in the head kidney and spleen of on-growing grass carp, the recommended MOS supplementation is 575.21, 557.58, 531.86, 597.35, 570.16, and 553.80 mg/kg, respectively. Collectively, MOS supplementation could alleviate oxidative injury in the head kidney and spleen of grass carp infected with Aeromonas hydrophila.